Thailand’s Response against Coronavirus Disease 2019: Challenges and Lessons Learned - Namwat, Chawetsan; Suphanchaimat, Rapeepong; Nittayasoot, Natthaprang; Iamsirithaworn, Sopon (OSIR Journal, 2020)
Since early January 2020, Thailand has been facing a rise in the number of patients infected with Coronavirus Disease 2019 (COVID-19), staring with imported cases from China then propagating to the Thai populations. The Thai Ministry of Public Health (MOPH) took a prompt response towards COVID-19 after the notification of the first case. Numerous strategic and operation plans were introduced. The plans comprise five key issues: (i) surveillance system, (ii) case management and hospital infection and control, (iii) laboratory testing, (iv) preparedness of healthcare staff and medical supply, and (v) risk communication. These plans are operated through the Emergency Operation Centre (EOC). A COVID-19 surveillance system at the airports and the hospitals was established. Criteria for identifying a patient under investigation (PUI) were set up. All confirmed COVID-19 cases are obliged to be isolated. Healthcare workers are recommended to wear appropriate personal protective equipment when taking specimens and providing care for the patients. Regarding laboratory testing, the Department of Medical Sciences (DMS) is the core unit in collaboration with other laboratory networks nationwide to ensure quality and standards of tests. The EOC operates all days and nights. Policy makers and high-level officers are obliged to meet together on a daily basis to provide strategic directions for the whole team. However several challenges remain. Fake news and stigmatization are amongst the most important concerns during the time of crisis. To tackle this, concerted effort needs be harnessed, from not only the health sector, but also all parts of the society including media and the Thai populations as a whole.    Keywords: COVID-19, SARS-CoV-2, Coronavirus, Thailand